Open space policy for landscape development In Malaysia - Ibrahim, Putri Haryati (International Institute of Islamic Thought East anf South East Asia & International Islamic University Malaysia, 2019)
Open space policy is set up with the intention to preserve open spaces for general public use. It was found that Sir Raymond Unwin was the first person to propose a space standard for the allocation of open spaces in London at the end of the 19th century. The standard developed by Unwin concentrated more on the suitable percentage of land units (open spaces) per person as a response to a minimal requirement of open space for a given population. The 'space standard' would later become known by its present name, 'open space policy'. The allocation for open space standard suggested by Sir Raymond Unwin became a popular planning tool and was adopted around the world because it is easy to be implemented since it is based on quantitative data. However, a further modified version of Sir Raymond Unwin's model, which included the criteria of open spaces, activities, size and residential density, was incorporated to fulfil users' needs. It can thus be said that the model set by Sir Raymond Unwin has been a key pillar in the introduction of an open space policy. It all started by taking into account what was thought to be the most appropriate size of open spaces that one required to feel comfortable in doing recreational activity onto fulfilling it to a perfection by integrating user's needs. The transformation of Unwin's model has taken into consideration how to satisfy users' calls for open spaces for recreational purposes. Thus, the placement of open spaces in landscape development in Malaysia must consider and accentuate activities, size, location and population density.